Influence of rootstocks on plant growth and internal quality of sweet orange (citrus sinensis) cv. Musambi - Aziz, Abdul; Hayat, Akbar; Ehsan-Ul-Haque; Khan, Muhammad Nawaz; Raza, Ahmed; Khadeja, Faheem; Ahmed, Maqsood (Journal of Pure and Applied Agriculture, 2023)
Musambi fruit is famous for its distinguished characters for taste and unique flavor in soil and climate of Punjab, Pakistan. The productivity of musambi is low which is greatly influenced by rootstock. Therefore, the experimental evaluation of rootstocks including exotic and local (rough lemon rootstock ) was done at Citrus Research Institute Sargodha.